A novel multi-drugs ciprofloxacin-curcumin-N-acetylcysteine co-delivery system based on hybrid nanocrystals for dry powder inhalations - Yingying Ma; Zhufeng Cong; Yancai Wang; Peng Gao (Next Nanotechnology)
This study designed a novel multi-drugs co-delivery system of ciprofloxacin-curcumin-N-acetylcysteine based on hybrid nanocrystals technology for dry powder inhalations (DPIs). The particle size of PVP k-30 stabilized curcumin nanosuspensions and Poloxamer 188 stabilized ciprofloxacin - N-acetylcysteine (NAC) hybrid nanocrystals was 219.2±4.6 nm and 346.3±7.3 nm, respectively (n=3). The curcumin nanosuspensions was solidified with ciprofloxacin - N-acetylcysteine (NAC) hybrid nanocrystals accompanied by the L-leucine to improve the dispersion of the DPIs. The dispersion, uniformity and fluidity of the spray-dried ciprofloxacin - N-acetylcysteine - curcumin (CPFX/NAC/Cur) nanosuspensions superior to the freeze-dried DPIs. The ciprofloxacin and curcumin of the CPFX/NAC/Cur DPIs obtained by spray-drying with mannitol was amorphous form, and thereby the dispersibility and solubility would be further improved. The four components complex DPIs delivery system designed in this study could give full play to the effects of each component, and then produce synergistic results. Therefore, this multi-drugs ciprofloxacin-curcumin-N-acetylcysteine co-delivery system based on hybrid nanocrystals has the potential to be used in the clinical treatment of pulmonary infections to improve the treatment effect and quality of life of patients.